Formation of narrative competence of a future doctor - T. V. Mescheryakova (Высшее образование в России)
In the article the author substantiates the necessity of formation of a narrative competence for future doctors. This competence should be considered as one of the manifestations of bioethics’ compensatory functions in medical practice. The given result has been obtained within the bounds of RFH grant № 12-03-00198 «Bioethics as a Form of Self-consciousness of Modern Culture» project. Also some results of the RFBR project № 10-06-00313 «Attractive Management: Methodological Principles of Managing Complex Systems’ Dynamics» are presented.